PENGGUNAAN LKS KOMIK UNTUK MENINGKATKAN PRETASI BELAJAR SISWA PADA POKOK BAHASAN KELARUTAN DAN HASIL KALI KELARUTAN (KSP) DI KELAS XI IPA SMA NEGERI 9 PEKANBARU - Pertiwi, Amelia Pertiwi; Rery, R Usman Rery (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The research aims to increase student learning achievement on the topic of solubility produk (Ksp) in class XI Science Senior High School (SMAN) 9 Pekanbaru. LKS comic dressed student is able to stimulate the brain while reading it, because it displays imagesthat are not boring for students while reading. The research is a kind of experiment research with pretest-posttest design. The samples of this research were the students of class XI Science4 as the experimental class and students of class XI Science3 as the control class. Experimental class is a class that is applied to LKS Komik  while the control class was not. Data analysis technique used is the t-test. Based on data analysis of data obtained tcount> ttable is 2.87>1.66, means that LKS use of comics can improve student learning achievement on the topic of solubility and solubility product (Ksp) in class XI Science Senior High School (SMAN) 9 Pekanbaru. The category improvement of student achievement at experiment class was high category with N-gain normalized is 0,77. Meanwhile, the category improvement of student achievement in control class was medium category with N-gain normalized is 0,64. Keywords:Learning Achievement, LKS Comics, solubility and solubility product (Ksp